2018
DOI: 10.1080/17461391.2018.1495768
|View full text |Cite
|
Sign up to set email alerts
|

Influence of upright versus time trial cycling position on determination of critical power and W′ in trained cyclists

Abstract: Body position is known to alter power production and affect cycling performance. The aim of this study was to compare mechanical power output in two riding positions, and to calculate the effects on critical power (CP) and W' estimates. Seven trained cyclists completed three peak power output efforts and three fixed-duration trial (3-, 5- and 12-min) riding with their hands on the brake lever hoods (BLH), or in a time trial position (TTP). A repeated-measures analysis of variance showed that mean power output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Cadence, body position as well as topography, i.e. level ground or uphill conditions, have also been shown to influence model parameter estimates due to different biomechanical recruitment patterns (Bertucci et al 2005 ; Kordi et al 2019 ; Nimmerichter et al 2012 ). Therefore, rider specialization (for example climber vs. time trial specialist) and race demands (uphill vs. flat, on-road vs. off-road, etc.)…”
Section: Deriving the Parameters Of Power-duration Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadence, body position as well as topography, i.e. level ground or uphill conditions, have also been shown to influence model parameter estimates due to different biomechanical recruitment patterns (Bertucci et al 2005 ; Kordi et al 2019 ; Nimmerichter et al 2012 ). Therefore, rider specialization (for example climber vs. time trial specialist) and race demands (uphill vs. flat, on-road vs. off-road, etc.)…”
Section: Deriving the Parameters Of Power-duration Modellingmentioning
confidence: 99%
“…Based on the current literature and the authors’ experience conducting power profiling in applied settings, the following recommendations can be made as a starting point for coaches and practitioners: to derive the parameters to model a power-duration curve a formal test protocol should include one sprint effort (i.e. ~ 10–15 s) and at least three maximum efforts between 2 and 15 min (Karsten et al 2015 ; Leo et al 2021a ; Muniz-Pumares et al 2019 ; Sanders and Heijboer 2019b ). These efforts can be completed in a single testing session, though it is recommended to divide field testing into two sessions over two consecutive days.…”
Section: Practical Recommendations In Applied Settingsmentioning
confidence: 99%
“…In this simulation study, some important real-world factors have not been considered. For example, it is well known that riding position can greatly affect power delivery abilities (in terms of critical power 42 ) and frontal area. 43 Usually (unpublished observation) riders stand out from the saddle when delivering high power output values and they typically ride on the hoods when they need to brake.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that by moving from riding on the hoods of the handlebars, to a time trial position, a rider's CP is reduced. 7 This reduction in CP is likely multifactorial and related to changes in oxygen consumption, muscle blood flow, muscle activation and gross efficiency. [8][9][10][11] For example, a lower hip angle may result in a reduction in muscle activity, 9 and subsequently power output 4 , in the lower limb owing to an alteration in the length tension relationship during the pedal cycle 9 .…”
Section: Introductionmentioning
confidence: 99%